PENGEMBANGAN MINIATUR LABUFER (STRUKTUR LAPISAN BUMI DAN ATMOSFER) BERBASIS AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN JAMBANGAN - Ainiatun Nafiah; Iis Daniati Fatimah (ELENOR: Elementary School Journal, 2024)
This research was conducted to determine the development process and the level of validity, practicality and effectiveness of learning media. The research aims to develop a miniature Labufer product (structure of the layers of the earth and atmosphere) based on audio visuals to improve the learning outcomes of class V students at SDN Jambangan. Product development is carried out using the ADDIE model which consists of five stages: analyze, design, develop, implement and evaluate. The data collection instruments used include validation sheets from material experts, media experts, teacher and student response questionnaires, and student evaluation test sheets. The validation test results show that the audio-visual-based Labufer Miniature (Structure of the Earth's Layers and Atmosphere) is very valid with a percentage of 94.5% from material experts, 94.7% from media experts, and 80% from language experts. The practicality test by the teacher showed a percentage of 87.2% which was declared practical and by students showed a percentage of 98% which was declared very practical. Meanwhile, the effectiveness test obtained a percentage of 87.5% which was declared effective. Based on the results obtained, the Miniature Labufer (Structure of the Layers of the Earth and the Atmosphere) audio-visual media developed is very valid, very practical and effective for use in the learning process. Keywords: Media, Labufer Miniatures, IPAS , Learning outcomes